Acquisition of Kosa Kata Bahasa Karo of a Four Year Karonese Child - Endamya Bevi Barus; Elia Masa Gintings (Universitas Negeri Medan, 2021)
Acquisition of Kosa Kata Bahasa Karo of a Four Year Karonese ChildEndamya Bevi Nesra Barus, Elia Masa GintingsUniversitas Negeri MedanAbstractThis study analyzed the acquisition of kosa kata Bahasa Karo of a fouryear old Karonese Child. The instrument of collecting data is by voice recordingof child in his daily activity. Particular attention is seeing aspects that affectchild’s acquisition as defined by using theory of Skinner, Behaviorist Theory. Theresult show that the child acquired 5 words of noun, 3 words of verb, 5 words ofadjective, 2 words of adverb, 2 words of pronoun, 1 word of preposition, 1 wordof conjunction, and 6 words of interjection. There are 2 aspects that affect child’sacquisition namely social interaction with his environment and imitation frompeople around him.Keywords: Child’s Acquisition Word, Skinner Theory, Karonese Child.